Some Properties Related With L^0 (Ω,F,μ) Space - Al-Mayahi, Noori; Jabar, Asawer (Al-Qadisiyah Journal of Pure Science, 2020)
The purpose of this paper is to investigate elementary properties of these measure and relation between these measure and we define a metric functions on the space of measurable functions and defined on finite measure space and we call the topology induced by p the topology of convergence in measure and we investigate now the connection between the convergence in metric of X and convergence in measure .